INTEGRATING THE FOUR BASES OF SUCCESS INTO STUDENT DEVELOPMENT WITH FIVE STEPS FOR WORLD CLASS STANDARD SCHOOLS - Kingsuwannapong, Nelawat (Journal of Bovorn Multi-Education and Human Social Sciences ( JOB_EHS ), 2025)
This article aimed to present the integrating the four bases of success (Iddhip da) into student development with five steps for world class standard schools. This was because education management in the 21st century was about preparing learners to have the skills necessary for living and being able to compete on the world stage, emphasizing the development of adaptability skills, lifelong learning, and living together happily. The International Standard School Project was therefore driven to develop and elevate the quality of education management to international standards, so that learners had the potential and abilities equal to learners from other countries. The development of learners to international standards could be done by organizing learning according to 5 steps, which was consisted of asking questions/hypotheses, searching for knowledge and information, creating knowledge, communicating and presenting effectively, and providing social and public service. Integrating the 4 principles of success (Iddhip da), which was consisted of desire, diligence, mind, and investigation, into the development of learners with 5 steps would help promoting the development of learners as a whole and sustainable.